Effects of recovery mode on power output in repeated bouts f short term, high intensity exercise - Connolly, D. A.; Baker, S. J (Medicine & Science in Sports & Exercise, 1997)
ATP repletion following exhaustive exercise is in the vicinity of 98-99% after three minutes of recovery. This quick recovery is crucial in repeated short bouts of intense work. What occurs in those three minutes could affect the level of recovery. This study evaluated changes in peak power, total power output, time to peak power, and lactate removal during repeated bouts of high intensity, short duration cycling under conditions of active and passive recovery. Six trials in each condition were assessed. There were no overall differences between each form of recovery however, the pattern of recovery across trials was different. Active recovery maintained higher levels of total power output longer than did passive recovery. Implication: Active recovery between short bouts of intense exercise sustains higher levels of power output than passive recovery.